ANALISIS PENDAPATAN USAHATANI JAGUNG DI DESA SIDONDO II KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Salma Salma; Effendy Effendy; Al Alamsyar (Jurnal Pembangunan Agribisnis (Journal of Agribusiness Development), 2022)
This research aims to find out how much the income of corn farming in Sidondo II Village, Sigi Biromaru District, Sigi Regency. This research was carried out in Jamuary to March. Determination of respondents was carried out using the simple random sampling method. The data collected in this study are in the form of primary and secondary data.The number of respondents determined as a sample in this study was 31 people from the total population of 102 people. The results of the analysis show that the average acceptance of corn farmer respondents is Rp.8.890.322,58/0,75ha /MT or equivalent to Rp.11.853.763,44 MT/ha, the average total cost of respondents to corn farmers is Rp.4.199.989,48/0,75ha /MT or equivalent to Rp.5.599.985,97/ha/MT, so that the income obtained by the respondents of corn farmers is Rp.4.690.333,10/0,75ha /MT or equivalent to Rp.6.253.777,47/ha/MT.